Crown Lengthening vs Forced Eruption - Singh, Ayush Razdan; Verma, Ruchita (Orthodontic Journal of Nepal, 2011)
Once the biologic width of the supporting periodontal attachment apparatus has been severely violated, more extensive procedures are often necessary to manage compromised root structure and supporting bone. Surgical techniques advocated are primarily corrective in nature and consist of root movement and repositioning or root removal and alteration of tooth morphology, with concomitant correction of the periodontium. Some indications for surgical corrective intervention to manage radicular perforations include extensive cervical resorption or traumatic perforation which extends well below the osseous crest in both single and multirooted teeth and damage to the furcation region of multirooted teeth which is not responding to nonsurgical therapy, is not amenable to simple surgical correction, or is complicated and compromised further by extensive periodontal disease. Common indications for orthodontic root extrusion include fractured tooth margins below crestal bone, deep carious margins, some isolated infrabony defects, and perforations from resorptions, post space preparation and aberrant access openings. When root extrusion is indicated to elevate a perforative root defect above the osseous crest; seldom is the desired result achieved without surgical crown lengthening. This is necessary to compensate for the coronal movement of the gingival attachment and alveolar bone which occurs with the tooth during eruption resulting in unacceptable esthetics. Although it is possible to extrude nearly any tooth the simplest cases are those that have single roots and an immediate proximal tooth on either side for appliance anchorage. Molars are generally difficult to treat as are the terminal teeth in the arch or free standing teeth.